Insurance status and time to completion of surgery for breast cancer. Issue 1 (19th April 2015) - Solomon, Matthew; Cochrane, Colin T.; Grieve, David A.
Abstract: Background: The aim of this study was to compare the time to re‐operation, following inadequate loco‐regional surgery for breast cancer, between the public and private sectors of the Sunshine Coast region. Methods: A retrospective review was performed of the medical records of all female patients undergoing guide wire‐localized, breast‐conserving surgery at Nambour General Hospital and in the local private sector from January 2009 until April 2010. The dates of initial consultation, operation, post‐operative consultation and any subsequent reoperation were recorded. Results: One hundred and seventeen public sector patients and 113 private sector patients were identified during the study period. Thirty‐seven public patients (32%) and 46 private patients (41%) required re‐operation. This difference was not significant (χ 2 = 2.06, degrees of freedom (df) = 1, P = 0.15). The mean time and standard error from the initial consultation to the first operation and re‐operation in the public sector was 26 (2.3) and 62 (3.8) days, and in the private sector was 12 (1.2) and 30 (4.4) days, respectively P < 0.001. On average, 70% of public patients and 96% of private patients completed the surgical component of their breast cancer management within the Queensland Health‐recommended time frame of 30 days (χ 2 = 26, df = 1, P < 0.001). Conclusion: While experiencing similar rates of re‐operative surgery in breast cancer management in the public and private sectors, the private sector deals with this issue in a more time efficient manner. An opportunity for intervention by quarantining theatre time is explored to improve the public sector time management.